2019
DOI: 10.1155/2019/3765282
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Lesion Characteristics Associated with Discordance between the Instantaneous Wave-Free Ratio and Fractional Flow Reserve

Abstract: Background. The instantaneous wave-free ratio (iFR) is an invasive coronary physiological index that is not inferior to fractional flow reserve- (FFR-) guided revascularization. The indexes of iFR and FFR are similar and closely correlated, but there are a few key differences. Previous studies suggested that patient characteristics and lesion severity could induce discordance between iFR and FFR. This study aimed to clarify the hemodynamics and lesion characteristics that influence discordance between iFR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Two randomized trials have demonstrated that iFR-guided treatment is non-inferior to FFR-guided treatment (11,12), while other NHPRs were not yet validated in randomized trials. However, discrepancies between NHPRs and FFR have been reported, and literature about this topic is growing (17,20,25), but still limited by a small number of examined patients (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two randomized trials have demonstrated that iFR-guided treatment is non-inferior to FFR-guided treatment (11,12), while other NHPRs were not yet validated in randomized trials. However, discrepancies between NHPRs and FFR have been reported, and literature about this topic is growing (17,20,25), but still limited by a small number of examined patients (26).…”
Section: Discussionmentioning
confidence: 99%
“…This might be caused by limitations such as the assumption of maximal flow and minimal resistance occurring during the wave-free period of the diastole, which is the rationale of iFR (17,18). Several clinical, angiographic, and hemodynamic factors contribute to iFR/FFR discordance (19)(20)(21). Available data do not represent a broader population in a real-world setting.…”
Section: Introductionmentioning
confidence: 99%
“…49 89 Other areas where discordance has been identified include the pattern of coronary disease (focal vs diffuse), 90 and patient characteristics such as gender, presence of diabetes mellitus and beta blocker use. [91][92][93][94] A summary of these discordant groups associated with FFR and iFR is presented in table 2.…”
Section: Controversies In the Use Of Nhprmentioning
confidence: 99%
“…Furthermore, we have previously reported that the prolongation of the QTUc during papaverine-induced hyperemia markedly lowered the iFR values [11]. However, the WFP is de ned as representing approximately 75% of mid to late diastole, excluding the initial 25% and the nal 5 msec, and neither myocardial activation nor the repolarization time changes the proportion of the WFP in diastole [8,21. The heart rate was an important factor accounting for the discrepancy between the ischemic diagnosis of FFR and the iFR because the heart rate only affected the iFR value and not the FFR value [22,23]. Therefore, distinguishing the low intracoronary resistance phase from the aortic pressure might be di cult.…”
Section: Discussionmentioning
confidence: 99%